Object oriented software methodology: a case st udy of systems for dam monitoring, state diagnosis and visualisation - Radomski, Aleksander; Gajl, Olaf (Computer Assisted Methods in Engineering and Science, 2023)
The complexity of the physical engineering objects requires new technologies in software development able to simulate real-life cases. The huge number of such cases can be covered by object-oriented paradigm. This general idea and some advantages of using object-oriented language (Smalltalk) are exemplified by a presentation of a system for earth dam control. The system is an expert type program equipped with advanced monitoring and visualisation functions for existing dams. The software development proces starting from the requirement description is presented. The structure of the dam model and of the inference engine as well as of the class hierarchy is shown as the examples. The re-usability of the system is proved by its implementation for different earth dams.